298 Effects of parity on late gestational uterine blood flow and hemodynamics in beef cattle. (5th December 2019) - Meyer, Allison M; Duncan, Natalie B; Stoecklein, Katy S; Stephenson, Emma L
Abstract: To determine parity effects on late gestational uteroplacental blood flow, uterine artery hemodynamics were measured in 13 primiparous and 11 multiparous (parity 3 and 4) non-lactating, fall-calving crossbred females beginning 109 d prepartum. Females were nutritionally managed as one group to meet or exceed nutrient requirements. Transrectal color Doppler ultrasonography of the both uterine arteries was conducted 3 to 6 times per female across late gestation, ending at approximately 20 d prepartum. Data were analyzed with parity (primiparous vs. multiparous), day prior to calving, and their interaction in the model; day was a repeated effect. Dam BW was greater (P < 0.001) for multiparous than primiparous females, and increased (P = 0.004) as gestation progressed. Calf birth weight was unaffected (P = 0.87) by parity. The parity x day interaction tended to affect (P = 0.06) ipsilateral uterine artery blood flow (L/min), where multiparous cows had a greater increase per day. Total and contralateral uterine artery blood flow were unaffected (P ≥ 0.11) by parity, but increased (P < 0.001) with day of gestation. When expressed relative to dam BW, total and contralateral blood flow were greater (P ≤ 0.04) in primiparous than multiparous females; ipsilateral blood flow was unaffected (P ≥ 0.13) by parity, however. Ipsilateral pulsatility index and both resistance indices were unaffected (P ≥ 0.28) by parity and day, but day tended to affect (P = 0.07) contralateral pulsatility index. Parity did not affect (P ≥ 0.11) cross-sectional area, mean velocity, peak systolic velocity, and end diastolic velocity of either uterine artery, but all increased (P < 0.001) as gestation progressed. Heart rate was greater (P = 0.03) in primiparous than multiparous females. Data suggest that uterine artery blood flow and heart rate may be altered in primiparous females, even when birth weight is unaffected by parity.